Radiopharmaceutical extravasations: a twenty year mini-review - Osborne, Dustin R. (Frontiers in Nuclear Medicine, 2023)
Interest and research into radiopharmaceutical extravasation concepts has risen with the3 increase in use of radiopharmaceutical therapies, growing access to novel molecular imaging4 agents, and recent regulatory controversies. This mini-review will examine the literature of the5 last twenty years to summarize the history of radiopharmaceutical extravastions, determine key6 trends in imaging and therapies, and highlight critical gaps in research that currently exist. The7 intent of this work is to provide a summary of this complex topic that helps build awareness and8 promotes new innovations in this interesting aspect of theranostic radiopharmaceuticals.